Pembuatan Serbuk Perak dengan Metode Reduksi Presipitasi Kimia dan Pasta Perak untuk Aplikasi Kontak Metal Sel Surya Silikon - Yunus Tonapa Sarungu (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Utilization of natural solar energy needs supporting technology to obtain maximum contertion of solar energy. Therefore, there its need to design a medium to absorb photothermal energy for further application. In this research, Synthesis of Silver Powder Using Chemical Reduction-Precipitation and Silver Paste for Metal Contacts Solar Cell Application The making of silver powder using precipitate reduction method with raw material from silver nitrate. Silver nitrate reduced by ascorbic acid then added by arabic gum as dispersant and potassium sulfate as modifier. PH of silver nitrate and reduction solution is kept by using HNO3. Reaction is happened at 25 oC (RTP). The purity of silver powder as result of reduction is analyzed by SEM (Scanning Electron Microscopy) & EDS (Energy Dispersive Spectroscopy) and XRD (X-ray Diffraction) and XRD (X-ray Diffraction). Result SEM (Scanning Electron Microscopy) & EDS (Energy Dispersive Spectroscopy) show that silver powder have purity almost 100 % with spherical particle. Result XRD (X-ray Diffraction) show that system crystal silver powder same with system crystal pure silver powder. Silver powder used for making silver paste with ethylene glycol, butyl acetate as solvent; hidroxy ethyl cellulose as resin binder; triton as additive; and silicate as glass frit. Metallization process of silver paste on silicon is carried out by screen printing method. The silver paste which has been metalized on silicon is analyzed using FPP (Four Point Probe) to know silver paste sheet resistivity. Result of analyze showing that silver paste has sheet resistivity 85,8 mΩ/sq.